EVALUASI PEMBELAJARAN BERBASIS TEKNOLOGI DALAM PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Wahyudi, Muhammad; Al-Fayed, Muhammad Rizky; ARIYANI, NINA; Yanti, Sherly; Sholikhatun, Tri; Salsabila, Aisya; Riadi, Akhmad (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2023)
Nowadays, incorporating technology into education, including PAI, has become a necessity. This study examines the application of technology-based learning in children's education (PAI) in the digital era. Through literature review and case studies, this study identifies the challenges and opportunities that arise with the application of this PAI. The results of the study show that technology has increased students' access to learning resources and increased their motivation to learn. However, challenges such as digital inequality, lack of teachers' ability to use technology, and lack of adequate infrastructure still need to be addressed. The purpose of this research is to create an effective technology-based learning model for Islamic religious education. This model combines [the components of the model, such as face-to-face learning, e-learning, and project-based learning]. Using [research methods], this study tests the feasibility and effectiveness of the model. The results of the study show that [e.g., the model created can improve students' understanding of the concept of religion]. This study helps develop innovative learning models that are in accordance with the requirements of Islamic religious education in the digital era.